(untitled) (Research, Society and Development, 2020)
Objective: describe the importance of organizing and participating in online scientific events in the training of undergraduate nursing students as a strategy to resolve the losses in the teaching and learning process, due to the COVID-19 Pandemic. Methodology: This is an account of the experience of a teacher and students of the Nursing Course at a private college in the State of Rio de Janeiro, who held a free Webinar for students, teachers and health professionals in order to raise awareness and warn about measures to combat violence against the elderly. The activity was carried out in July, organized in two stages: the first included the organization of the event with periodic meetings on digital platforms and construction of promotional material and social media. After the planning stage, the event took place in an Online Platform, providing access to participants after prior registration and registration on the website. Results and Discussion: On the day of the event, there were 238 registrations, including participants from the Southeast, Northeast and North regions. Following the University’s regulations for booking online activities, 109 participants were booked with a workload equal to or above 50%. Conclusion: online education actions allow students who are going through remote teaching to expand their learning horizons by having the opportunity to listen and participate in scientific events with qualified professionals in the study area.